Integrative molecular and pathologic profiling of triple negative breast cancer - Alsaleem, Mansour (2021)
Introduction: Breast cancer (BC) is a heterogeneous disease presenting with variable morphologies, molecular profiles, clinical behaviours and responses to therapy. Triple negative breast cancer (TNBC), characterised by the absent expression of the Oestrogen Receptor (ER), Progesterone Receptor (PR) and HER2 overexpression, is an aggressive class of BC for which targeted therapies are lacking. Patients with TNBC comprise approximately 17% of BC patients and show variable responses to chemotherapy, which reflects the transcriptomic and genomic heterogeneity of the disease. In this study, we hypothesised that deciphering TNBC molecular heterogeneity can pave the way for the identification of novel therapeutic targets and the refinement of classification. We investigated large, well annotated cohorts of TNBC using a variety of molecular techniques to: 1) identify genetic predictors of clinical outcomes in TNBC, 2) investigate the mechanistic and prognostic role of novel targets in TNBC including periplakin (PPL), 3) further evaluate the mechanisms of cell adhesion in TNBC.